PENGARUH LINGKUNGAN BELAJAR DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN (PKK) SISWA SMKN 3 KOTA BLITAR - Hadi Sucipto, Hadi Sucipto; M. Anas, M. Anas; RR. Forijati, RR. Forijati (Fakultas Ekonomi Universitas 45 Surabaya, 2020)
The purpose of this study was to examine the effect of learning discipline and learning environment on learning outcomes of Creative Products and Entrepreneurship (PKK) students of SMKN 3 Blitar City in the odd semester of the 2018/2019 school year. This research uses descriptive analysis method, while inferential statistical analysis is multiple regression or change to find out the magnitude of the influence between the discipline of learning in school and the learning environment on learning outcomes. The conclusions of the results of this study are (1) The effect of the learning environment partially on the learning outcomes of the Creative Products and Entrepreneurship (PKK) students of SMKN 3 Blitar City in the odd semester of the 2018/2019 school year, (2) The effect of partial learning discipline on learning outcomes Creative and Entrepreneurship Product subjects (PKK) of SMKN 3 City Blitar students in the odd semester of the 2018/2019 school year, (3) The effect of simultaneous learning discipline and learning environment on learning outcomes of Creative and Entrepreneurship Product subjects (PKK) of SMKN 3 City students Blitar in the odd semester of the 2018/2019 school year